The Influence of Service Innovation and Brand Image on Customer Loyalty in the Indonesian Ride-Hailing Industry: English - Listyanti, Anindita Ayu; Heriyadi; Ramadania; Pebrianti, Wenny; Ahmadi (Yayasan Sinergi Kawula Muda, 2025)
The ride-hailing sector in Indonesia has experienced significant growth, making service innovation and brand reputation crucial for cultivating customer loyalty. This study investigates the effects of service marketing innovation and corporate brand image on customer satisfaction and their subsequent influence on customer loyalty. This research utilises survey data from 261 individuals across three major ride-hailing platforms—Grab, Gojek, and Maxim—employing SmartPLS 4.0 to evaluate the proposed relationships. The findings demonstrate that service marketing innovation and corporate brand image positively influence customer satisfaction, enhancing customer loyalty. Furthermore, trust and perceived value significantly impacted consumer satisfaction and loyalty, highlighting the essential importance of these factors in maintaining competitive advantage in the ride-hailing industry. The study suggests firms must prioritise innovative service strategies and strong brand positioning to foster lasting customer loyalty.